Negotiating Tradition and Modernity: The Pedagogy of Mahabbah in Developing the Character of Millennial Students at the Bahrul Ulum Tambakberas Islamic Boarding School in Jombang - Sandi Ferdy Yulianto; Ahmad Barizi; Sufirmansyah Sufirmansyah; Ninik Zuroidah; Muhammad ‘Imaduddin Roshief (Nuris Journal of Education and Islamic Studies, 2026)
The shift in educational values in the digital era has added further strains between the traditional authoritarian pedagogy and the reflective and egalitarian nature of millennial learners. This research will explore the role of mahabbah pedagogy as an affective–relational process of negotiating this tension during character education in pesantren. The research contribution is that it conceptualizes mahabbah pedagogy as an affective-relational pedagogical framework and provide empirical evidence of its role in mediating the relationship between tradition and modernity in Islamic education. This research is a qualitative study that relies on an intrinsic case study design that is conducted at Bahrul Ulum Tambakberas Islamic Boarding School, Jombang. Purposive and snowball sampling methods were used to collect data by way of participatory observation, semi-structured interviews with kiai, ustaz, and santri, and documentation. Inductive data analysis was done using data reduction, displaying data and drawing conclusions. The results indicate that mahabbah pedagogy is reflected in the affective relationships that are empathetic, emotionally close, and trustful, which create a dialogical and reflective learning environment. It acts as a relational process of cultural mediation and the mitigation of tensions between hierarchical traditions and egalitarian learner attributes. Moreover, it encourages transformative reflection by the methods of self-knowledge and internalization of values. The study presents three fundamental elements, namely, affective relationships, cultural mediation, and transformative reflection, that conglomerate to create the wholeness of character development of santri. Finally, mahabbah pedagogy presents a theoretically based and practically applicable model in the development of humanistic, adaptive and transformative education, and in providing a platform upon which future integration can be achieved within digitally mediated learning environments.